The Influence of Hobbes and Locke in the shaping of the concept of sovereignty in eighteenth-century France - Wilson, I (Voltaire Foundation, 2017)
I. Hobbes: a synopsis of his doctrine relative to sovereignty II. Locke: a synopsis of his doctrine in relation to the concept of sovereignty III. The Diffusion of Hobbes's views on the concept of sovereignty in French political thought before 1735 IV. The Diffusion of Locke's political theories in French political thought before 1735 V. Barbeyrac on Hobbes VI. Barbeyrac on Locke VII. The Influence of Hobbes on Montesquieu VIII. The Influence of Locke on Montesquieu IX. Hobbes in the Encyclopédie X. Locke in the Encyclopédie XI. Hobbes in the French and Dutch gazettes, 1735-1767 XII. Locke in the French and Dutch gazettes XIII. Hobbes in Burlamaqui XIV. Hobbes in Réal de Curban XV. Locke in Réal de Curban XVI. Hobbes in Martin Hübner XVII. General references and allusions to Hobbes in the period 1735-1767 XVIII. General references and allusions to Locke in the period 1735-1767 XIX. Hobbes and his influence on Rousseau XX. Locke and his influence on Rousseau XXI. Hobbes: conclusion XXII. Locke: conclusion Bibliography